PEMBERDAYAAN USAHA KECIL DAN MENENGAH (UKM) PRODUK PANGAN TRADISIONAL DENGAN TEKNOLOGI DIGITAL DI KELURAHAN SARIO KOTABARU, KOTA MANADO - Tooy, Dedie; Longdong, Ireine Adriana; Pinatik, Herry Frits; Lengkey, Lady E.Ch.; Koapaha, T.; Mamuaja, Christine; Laleleh, Sherina; Walangitan, Khesilya E.; Mona, Frits (Jurnal Abdimas Bina Bangsa, 2024)
Small and medium-sized enterprises (SMEs) in traditional food processing often face challenges such as limited marketing channels that rely mostly on word-of-mouth with restricted reach, unstructured financial management, and monotonous business activities. This Community Partnership Program (PKM) was conducted in Sario Kotabaru Village, Sario District, Manado City, targeting two SMEs that produce and sell traditional North Sulawesi foods, specifically "tinutuan" porridge combined with vegetables and pumpkin, and traditional fried snacks such as "nike" fritters and corn fritters, which are highly nutritious. The goal of this PKM activity was to provide training and motivation to the partners in digital marketing, sanitation, and financial management, enabling them to expand their business operations and increase profitability. The training included sessions and assistance on the importance of food sanitation, digital product marketing strategies, and financial management. The implementation method consisted of three stages: survey, proposal preparation, and submission; followed by coordination, socialization, and training in the second stage; and finally, evaluation and reporting. The PKM materials covered branding, marketing strategies, and food sanitation, including the use of social media for digital marketing and internet-based financial management software. The results showed that the targeted SMEs gained an understanding and hands-on experience with digital marketing using mobile phones, received support for digital content creation, and applied improved sanitation practices, contributing to a positive brand image. Evaluation results through questionnaires show that there is a change in mindset, skills proven by questionnaire responses after training with high levels of understanding